Mechanochemical Synthesis and Characterization of conductive Polyaniline Catalyzed by Maghnite-H+ (Algerian Montmorillonite) - Abdelkader, Rahmouni; Amine, Harrane; Mohammed, Belbachir (International Journal of Advanced Chemistry, 2013)
Conductive polymers had been the topic of the large number of investigations during last decades because of their unique properties such as mechanochemical strength, electrical conductivity, corrosion and thermal stability. Maghnite-H+ is a montmorillonite sheet silicate clay, which exchanged with protons. Polyaniline (PANI), with unique electrical and optical properties, is a promising candidate for wide range of potential applications. So that, in the present paper we report:1-Synthesis of polyaniline by chemical polymerization of aniline using montmorillonite (Mag-H+) as Protonic source.2- Different oxidant such as (K2S2O8Â , K2Cr2O7Â , CuCl2).3- Characterization of different polyaniline by different technics.With these easy synthesis associated good solubility, thermal stability and high electrical conductivity.